RG Veda. Book 2 - Furukawa, Haruko; Dashiell, Christine, 1984-; IHL (Letterer); Horn, Carl Gustav (Dark Horse Comics, 2017)
RG Veda, pronounced Rig Veda, is based on the classic Indian saga of the same name.